Проявления предменструального синдрома: особенности в разных возрастных группах у спортсменок в ряде видов спорта - Бугаевский, К. А.; Черепок, А. А.; Бугаєвський, Костянтин Анатолійович; Черепок, Олександр Олексійович; Bugaevsky, K. A.; Cherepok, O. O. (My University, 2018)
В статье представлены результаты лонгитюдного исследования, посвящённого изучению особенностей соматических и психологических проявлений предменструального синдрома у спортсменок разных возрастных групп и в разных видах спорта. Представлены сравнительные данные отечественных и зарубежных исследователей, занимающихся этой проблемой, описаны варианты становления и развития предменструального синдрома в каждой из обследованных возрастных групп. Определено, что во всей обследованной группе разнообразные соматические проявления предменструального синдрома были у 222 (74,00%) спортсменок, а психологические проявления предменструального синдрома были зафиксированы у 192 (63,00%) спортсменок. Установлено, что комбинированные проявления предменструального синдрома со средне и значительно выраженными сомато-психологическими и психо-соматологическими проявлениями предменструального синдрома были определены у 194 (64,67%) спортсменок, в трёх обследованных возрастных группах. У статті представлені результати лонгитюдного дослідження, присвяченого вивченню особливостей соматичних і психологічних проявів передменструального синдрому (ПМС) у спортсменок різних вікових груп і в різних видах спорту. Представлені порівняльні дані вітчизняних та зарубіжних дослідників, що займаються цією проблемою, описані варіанти становлення та розвитку ПМС в кожній з обстежених вікових груп. Визначено, що з урахуванням проведення аналізу отриманих результатів у всій обстеженій групі різноманітні соматичні прояви ПМС, були визначені у 222 (74,00%) всіх спортсменок, а психологічні прояви ПМС, були зафіксовані у 192 (63,00%) спортсменок. Встановлено, що комбіновані прояви ПМС, з середньо вираженими і значно вираженими сомато-психологічними і психо- соматологічними проявами ПМС, були визначені у 194 (64,67%) всіх спортсменок в трьох обстежених вікових групах. In recent years the issue of premenstrual syndrome, with its variety in somatic and psychological manifestations (both psychosomatics and somatopsychology) has been paid to much attention of gynecologists, endocrinologists and psychologists.Nevertheless, there are only few reports on the study of premenstrual syndrome in female athletes of different age groups, this is especially true for Ukrainian sports medicine. This article presents the results of a longitudinal study on the characteristics of somatic and psychological manifestations of premenstrual syndrome (PMS) in female athletes of different age groups and in various sports. The article provides the comparative analysis of the data reported by national and international researchers on this problem; describes the variations in the PMS development in each of the examined age groups. It has been found out based on the analysis of the obtained results, various somatic PMS manifestations are identified in 222 (74.00%) of all athletes, and the psychological PM manifestations are typical for 192 (63.00%) athletes, while combined PMS manifestations with moderately pronounced and significantly pronounced somato-psychological and psycho-somatological manifestations of PMS, were identified in 194 (64.67%) of all female athletes in the three age groups studied. Analysis of the study results has shown the most pronounced PMS manifestations are found in groups of athletes of juvenile and I reproductive age. Thus, among young athletes representing 10 sports, somatic PMS manifestations of PMS were detected in 127 (81.94%) athletes, psychological manifestations were detected in 109 (70.32%) athletes, and combined manifestations – in 111 (71.61%) athletes. 34 (87.18%) athletes of this group demonstrate somatic PMS manifestations, equal shares 29 (74.35%) of athlets have psychological combined PMS manifestations. The data of additional interviewing and the results of the survey directly indicate a significant prevalence of PMS in all types of modern women's sports and in all age groups, being the factor, that significantly decrease in the performance of athletes, both in the competitive and in the training period of their activities.
Прояви передменструального синдрому: особливості у різних вікових груп у спортсменок в ряді видів спорту
Manifestations of premenstrual syndrome in different age groups of female athletes presenting different sports
Keywords: спортсменки; пубертатный возраст; юношеский возраст; І репродуктивный возраст; предменструальный синдром; соматические и психологические проявления; пубертатний вік; юнацький вік; І репродуктивний вік; передменструальний синдром; соматичні та психологічні прояви; female athletes; pubertal age; adolescence; reproductive age; premenstrual syndrome; somatic and psychological manifestations